Analisis Kerusakan pada Chain Link Apron Feeder - Muhammad Surya Netrane Jagad Jagad; Nurhabibah Paramitha Eka Utami; Diah Kusuma Pratiwi (Universitas Sriwijaya, 2021)
The use of an Apron feeder with a carrying capacity of 90 tons with a motor with a power of 55 KW and engine speed of 1500 RPM as a container for coal unloading results in train cars and then distributed to a belt conveyor for 24 hours. Based on Standard Operating Procedures (SOP), the apron feeder can accommodate 8 train carriages for 120 minutes of unloading coal. This process initiates the possibility of fatigue in the Apron feeder component, namely the chain link. This study aims to determine the cause of chain link damage in terms of micro structure and strength to the value of hardness by using chain link analysis samples from PT. Acid Hill. Metallographic testing showed the presence of a banded structure in the new sample and the presence of a martensite phase in the damaged sample material, causing the material to become stronger but brittle.